The Role of Muhammadiyah Cadres in the Decision to Register Students at the Muhammadiyah Boarding School (MBS) Selong, East Lombok - Hartiani Hartiani; Muhammad Attha Iqbal; Nurmaulia Khotmi; Diarti Hariani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
The Muhammadiyah boarding school (MBS) in Selong, part of Muhammadiyah's philanthropic educational institution, faces significant challenges marked by stagnant student enrollment. After four years of operation, the institution only accommodates 68 students amidst a persistent downward trend, despite a broad network of Muhammadiyah cadres throughout East Lombok. This qualitative-descriptive study aims to examine three dimensions: the role of Muhammadiyah cadres in shaping enrollment decisions, the factors driving these decisions, and strategic steps to optimize cadre involvement in institutional promotion. Data were collected through in-depth interviews, participant observation, focus group discussions, and documentation analysis. The findings identify four key cadre roles: information agents, local opinion leaders, trust brokers, and decision facilitators. Enrollment decisions are shaped by rational factors such as perceived educational quality, tuition fees, physical facilities, and the institutional appeal of MBS Selong as a modern Islamic boarding school capable of integrating formal general academic education, religious instruction, and competitive extracurricular programs into a cohesive educational framework, social recommendations, and emotional closeness to cadre figures. This study contributes a new conceptual framework by integrating educational consumer behavior theory with community-based da'wah mobilization, introducing the concept of da'wah-based marketing actors as a new analytical lens for understanding student selection behavior in the context of the Muhammadiyah organizational ecosystem.